2020
DOI: 10.1111/ijd.14805
|View full text |Cite
|
Sign up to set email alerts
|

Association of metabolic syndrome with pediatric psoriasis: a case‐control study in Kabul, Afghanistan

Abstract: Background Limited studies have assessed the risk of metabolic syndrome in pediatric psoriasis. This study was aimed to investigate the association of obesity and metabolic syndrome with pediatric psoriasis in Afghanistan. Methods A case‐control study was conducted from March to December 2018 at the dermatology department of Maiwand Teaching Hospital in Kabul city. Participants were children aged less than 18 years; 113 children with psoriasis and 113 children without psoriasis were compared. Height, weight, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…All studies reported the pooled prevalence of MetS among patients with psoriasis; of them, 15 described this prevalence in men and women, 38 reported the prevalence in adults, 15–22,24–26,28,29,31–36,38,40–44,46–52,54–57,59 and 4 reported the prevalence in children and teenagers 30,37,53,58 . Fifteen studies 17,19–22,32,34,37,38,40,44,45,49,50,59 analysed the prevalence of combined MetS in patients with mild, moderate and severe psoriasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies reported the pooled prevalence of MetS among patients with psoriasis; of them, 15 described this prevalence in men and women, 38 reported the prevalence in adults, 15–22,24–26,28,29,31–36,38,40–44,46–52,54–57,59 and 4 reported the prevalence in children and teenagers 30,37,53,58 . Fifteen studies 17,19–22,32,34,37,38,40,44,45,49,50,59 analysed the prevalence of combined MetS in patients with mild, moderate and severe psoriasis.…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported the pooled prevalence of MetS among patients with psoriasis; of them, 15 described this prevalence in men and women, 38 reported the prevalence in adults, [15][16][17][18][19][20][21][22][24][25][26]28,29,[31][32][33][34][35][36]38,[40][41][42][43][44][46][47][48][49][50][51][52][54][55][56][57]59 and 4 reported the prevalence in children and teenagers. 30,37,53,58 Fifteen studies 17,[19][20][21][22]32,34,37,38,40,<...…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…As depicted in Table 1, 21 studies examined the relationship between MetS and psoriasis with a total population of 11,826 patients. All studies had an average age range between 35 and 53 years old, except one study in which children with an average age of 13 years old were under investigation 48 . Ninteen of 21 studies recorded that psoriasis patients are greatly more affected by MetS 29–32,35–49 .…”
Section: Resultsmentioning
confidence: 99%
“…one study in which children with an average age of 13 years old were under investigation. 48 Ninteen of 21 studies recorded that psoriasis patients are greatly more affected by MetS. [29][30][31][32][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Howbeit, statistical analysis results, following the removal of adjusted variables in one study, were altered.…”
Section: Vitiligomentioning
confidence: 99%
“…In an anthropometric survey of 113 children with psoriasis and 113 healthy children in Kabul (Afghanistan), researchers found that children with psoriasis had higher body weight and central obesity than children in the control group (27.4 % vs. 12.4 %, OR=2.67; р=0.005 and 23 % vs. 9.7 %, OR=2.77; р=0.007, respectively). In addition, sick children had higher family history of skin diseases (23.0 % vs. 13.7 %; р<0.001) [1]. The importance of such a factor in the development of psoriasis as body weight and the presence of obesity in children is emphasized by the results of other studies [21].…”
Section: Indicatorsmentioning
confidence: 91%